2021
DOI: 10.1152/jn.00623.2020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of intermediate reticular formation involvement in swallow pattern generation, recorded optically in the neonate rat sagittally sectioned hindbrain

Abstract: Swallow is a primitive behavior regulated by medullary networks, responsible for movement of food/liquid from the oral cavity to the esophagus. To investigate how functionally heterogeneous networks along the medullary intermediate reticular formation (IRt) and ventral respiratory column (VRC) control swallow, we electrically stimulated the nucleus tractus solitarius to induce fictive swallow between inspiratory bursts, with concurrent optical recordings using a synthetic Ca2+ indicator in the sagittally-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…Diaphragm activity has been shown to be multimodal, having different activity patterns for swallow and breathing, including concurrent inhibited respiratory related activity and activated swallow related activity, Schluckatmung , in physiologic and fictive swallows (Huff et al, 2022; Pitts et al, 2021; Pitts et al, 2018). Activation of glutamatergic neurons in the area of PiCo resulted in swallow related diaphragmatic activation, Schluckatmung .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diaphragm activity has been shown to be multimodal, having different activity patterns for swallow and breathing, including concurrent inhibited respiratory related activity and activated swallow related activity, Schluckatmung , in physiologic and fictive swallows (Huff et al, 2022; Pitts et al, 2021; Pitts et al, 2018). Activation of glutamatergic neurons in the area of PiCo resulted in swallow related diaphragmatic activation, Schluckatmung .…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the SPG activates pre-motor neurons in the dorsal respiratory group responsible for diaphragm recruitment during swallow (Pitts et al, 2018). Inspiratory neurons of the medial reticular formation have been shown to increase firing frequency during Schluckatmung (Pitts et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether they might coordinate the observed distributed initiation of inspiratory bursts, a broad-spectrum synaptic blocker cocktail was applied, silencing respiratory motor output within 2 min of drug application. Patency of blockade was validated by showing that following synaptic blockade, post-synaptic networks mediating swallow were no longer activated by stimulation of putative command networks for swallow in dorsomedial medulla [ 19 ] (Video in Additional file 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…These brainstem networks are considered critical correlates of the developing neural swallowing control. Recently, Pitts and colleagues [2021] used an in vitro neonatal rat model to examine the role of the swallow CPG, as well as additional areas in the medulla (specifically, the medullary intermediate reticular formation (IRt) and the ventral respiratory column (VRC)), in eliciting cranial nerve responses indicative of a fictive swallow and/or a breathing reflex [44]. Critically, they found that, in addition to neurons within the swallow CPG, new networks within the IRt, near the facial nucleus in the dorsal medulla, were also active during the swallows.…”
Section: Lessons From Recent Animal Studiesmentioning
confidence: 99%